Determining optimal practices for foal weaning – A protocol for a systematic review and network meta-analysis - Nicole Cranston; Petra Buckley; Lorraine Rose; Jaymie Loy; Hayley Randle (PLoS ONE, 2026)
Background Weaning is a stressful time in a foal’s ( Equus caballus ) life. As humans artificially manage weaning in domestic horses, it provides an opportunity to safeguard horse welfare early in life, with potential long-term benefits. While numerous studies have examined the effects of different weaning and management interventions on foal stress, optimal weaning practices have yet to be identified. Overall purpose of the study: To identify which weaning interventions and management practices have the greatest potential to improve foal welfare based on physiological and behavioural outcomes. Research questions: (1) What physiological and behavioural changes occur in foals in response to artificial weaning? (2) Do different interventions during weaning produce different physiological and behavioural outcomes in foals? (3) How do study-level characteristics explain heterogeneity in foal outcomes during weaning, and which impact welfare outcomes across different interventions? (4) Which interventions, management practices, or combinations thereof most effectively optimise foal welfare during weaning? Methodology Six databases were searched on 24 August 2025. Database search strings were based on the Population-Intervention-Comparator-Outcome (PICO) framework and were PRESS-reviewed. Additional studies, including grey literature, will be identified through dissertation databases, ScienceDirect, Google Scholar, and by hand-searching the reference lists of included studies and narrative reviews, to ensure a comprehensive search. Articles will be selected based on predefined eligibility criteria. Two reviewers will independently conduct title/abstract and full-text screening, data extraction, and assess risk of bias and confidence in the evidence (GRADE and CINeMA). Results will be synthesised through pairwise and Bayesian network meta-analysis using R Statistical Software. Conclusion This systematic review will be the first to investigate foal welfare during artificial weaning, and the findings are expected to provide evidence-based recommendations to improve foal welfare. This paper outlines the protocol that will be used and does not contain any empirical results. Registration This systematic review protocol was registered on the Open Science Framework (OSF) on 19 May 2025 ( https://doi.org/10.17605/OSF.IO/DJWQY ).